Vertical Bonegraft Wrap: técnica para aumento de volume de tecido mole em região paranasal - Muller, Leonardo Luiz (2020)
Introduction: Orthognathic surgeries consist of osteotomies that provide harmonious angles to the face. Widespread in the literature, they present indications such as seeking an adequate occlusion, promoting a favorable airway space, correcting discrepancies and facial asymmetries, returning function and promoting a pleasant aesthetic. Through osteotomies, such as the Le Fort I osteotomy in the maxilla, the movements of advancing, impaction and retreat of bone stumps can be performed. The use of granulated xenogenous bone graft wrapped by a membrane aims to improve the support, position and volume of the soft tissue of the face. This technique can be used in orthognathic surgery and has already been described in the literature.Objective: To demonstrate the Vertical Bonegraft Wrap technique to increase the volume of soft tissue in the paranasal region. Technique report: Patient C.R.B. 49 years old, male, with Class III dentofacial deformity and severe anteroposterior deficiency of the maxilla, underwent Le Fort I osteotomy in the maxilla, with maxillary advancement of 10 mm. After stable internal fixation with titanium plates and screws, Cerabone Block® fixed with screws was used in order to fill the gap in the anterior region of the maxilla, promoting stability. In order to attenuate the patient's paranasal deficiency, the Vertical Bonegraft Wrap technique was used. The technique consists of using Cerabone Granulate® wrapped in Jason Membrane® in the Le Fort I osteotomy region, placed vertically in the paranasal region. Postoperative tomographic evaluations of 14 days and 6 months, linear and volumetric analyzes demonstrated good healing, good adaptation and, above all, good consolidation in the region, as well as volume gain and maintenance in the grafted area with low absorption rate. Conclusion: The use of the vertical bonegraft wrap technique proves to be effective due to easy manipulation, facial reproduction of the technique and mainly presents a significant volume gain in the paranasal region